Characteristic of Antioxidant-Rich “Teh Talua” Instant Using the Foam Mat Drying Method - Rasdiana, Felga Zulfia; Ismed, Ismed; Refdi, Cesar Welya; Fauzi, Yusma Resti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This research aims to determine the formulation and characteristics of the best instant “teh talua” with the addition of red ginger and areca nut. In this study, 5 treatments were used, namely without addition (control), with the addition of red ginger juice (5% and 10%), and with the addition of areca nut extract (5% and 10%). The data obtained were subjected to statistical analysis using Analysis of Variant (ANOVA) and continued with Duncan's New Multiple Range Test (DNMRT) at a significance level of 5%. The results showed that each treatment had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, water activity (Aw), and antioxidant activity. The best treatment is treatment B (with the addition of red ginger juice 5%) with a water content of 17.90%, ash content of 1.58%, protein content of 3.09%, fat content of 12.39%, carbohydrate content of 64.98%, water activity (Aw) 0.523%, and antioxidant activity 54.98%.